The Impact of Therapeutic Communication on Patient Satisfaction in Community Health Centers - Nurul Jannah; Arif Budiwibowo; Anas Kiki Anugrah; Sri Yuliana; Karim Sahidun (JURNAL KESEHATAN PRIMER, 2026)
Background: Therapeutic communication is an essential component of healthcare services because it contributes to building trust between healthcare providers and patients, enhances patient understanding, and creates a higher-quality care experience. However, variations in the quality of communication across healthcare facilities can lead to decreased patient satisfaction and lower perceived service quality. Objectives: This study aimed to analyze the relationship between therapeutic communication and patient satisfaction levels in the service area of BLUD Woha Community Health Center. Methods: The study employed a cross-sectional design and was conducted at the Woha Community Health Center. Sampling was carried out using an accidental sampling technique, resulting in 92 respondents. Data were collected through questionnaires to assess therapeutic communication and patient satisfaction. Data analysis was performed using Spearman’s rho correlation test with a significance level of 0.05. Results: The results showed that therapeutic communication was most commonly categorized as moderate, with 45 respondents (48.9%). Meanwhile, patient satisfaction was predominantly in the low category, with 59 respondents (64.1%). The correlation test yielded a value of r = 0.689 with p = 0.001. Conclusions: Therapeutic communication has a significant relationship with patient satisfaction. Therefore, it is recommended that healthcare facilities strengthen therapeutic communication training, conduct regular supervision, and incorporate communication indicators into service performance evaluations.